Developing Instruments to Measure Project-Based Learning in the Course of Teaching English to Young Learners Program Development - Fatimah, Nur; Soviyah, Soviyah (Ahmad Dahlan Journal of English Studies, 2023)
Courses in TEYL (Teaching English to Young Learners) at the tertiary education level have been conducted in different universities including at the English Department of Universitas Ahmad Dahlan. One of the courses is TEYL Program Development (TEYL PD). It is to develop materials and/or program in TEYL. Since there’s not yet specific and detailed information regarding its assessment in the class of TEYL PD implementing project-based learning, this research aims to design instruments to measure the learning achievement in TEYL PD course. This research utilizes Research and Development (R&D) with ADDIE model. The development process encompasses five steps i.e. analyze, design, develop, implement, and evaluate. There are two rubrics resulted for the course to assess the students in doing the project on TEYL PD. The first is the rubric to assess group’s performance and the second is the one to measure individual performance related to the group project. The instrument for the group performance contains 7 aspects (stages of the project, data collection, target accomplishment, reporting, knowledge, attitudes, and skills). Individual performance was based on peer ranking on the aspects on the students’ contribution, collaboration, discipline and communication.  At this preliminary study, implementing the instruments was conducted by the test of readability and content validity by an expert in English language teaching. Further, the evaluation was realized based on their feedback. Further research is in demand to investigate the use of the instruments in the classroom setting on TEYL PD course.